Fusion of ASTER satellite imagery, geochemical and geology data for gold prospecting in the Astaneh granite intrusive, West Central Iran. (2nd January 2022) - Moradpour, Hooman; Rostami Paydar, Ghodratollah; Feizizadeh, Bakhtiar; Blaschke, Thomas; Pour, Amin Beiranvand; Valizadeh Kamran, Khalil; Muslim, Aidy M; Hossain, Mohammad Shawkat
ABSTRACT: In this study, ASTER imagery, geochemical, lithological, and structural data are exploited for Mineral Potential Mapping (MPM) of the Astaneh granitic pluton and its surrounding area. The independent component analysis (ICA) and Matched Filtering (MF) techniques are applied to ASTER data for detecting alteration mineral assemblages. Sericitically argillically altered minerals associated with jarosite and chlorite/epidote are mapped using the ICA technique. MF fraction images derived from n-dimensional visualisation (n-DV) tool facilitated detecting goethite, haematite, limonite, muscovite, kaolinite, illite, chlorite and epidote associated with gold occurrences. The distribution of Cu, Pb, Zn and Au is considered for generating geochemical anomaly layers. Strong Cu, Zn and Au anomalies are found to be associated with gold mineralisation. The lithological units hosting gold mineralisation and intersection of NE–SW and NW–SE trending lineaments are also considered. Fuzzy Logic Model (FLM) was used to generate gold prospectivity map for the study area by fusing the alteration, geochemical, geology and structural layers. Several high prospective zones are identified in the central and southeastern part of the study area. A majority of delineated exploration targets are either linked to the plutonic body or its surrounding metamorphic rocks. This study demonstrated a viable approach for future gold prospecting in the study area.